SOFT SKILLS NEEDED FOR THE TOURISM INDUSTRY (THE CASE OF BULGARIA) - Kyurova, Vyara; Kiryakova-Dineva, Teodora; Chankova, Yana (Europa del Este Unida, 2021)
Over the decades the tourism and hospitality industry has become one of the fastest-growing economic sectors in the world and it not only opens millions of job positions but also requires a lot of new approaches in educational training and practice. Within the wide range of services, there is often a lack of closer relations between the skills needed and the competences acquired by tourism students and specialists. Whereas some hard skills are traditionally taught at the educational institutions, other skills, called soft skills, often remain beyond the educators’ aims. This paper relates soft skills to the educational background of the prospective specialist in the field of tourism and aims at identifying the soft skills of ‘critical’ and of ‘considerable’ importance based on the opinions of three groups of respondents in Bulgaria.